2011
DOI: 10.1002/aic.12312
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the separation of sulfur hexafluoride and nitrogen by selective adsorption using monte carlo simulations

Abstract: We present molecular simulations to find the optimal conditions for the separation by adsorption of SF 6 from a gaseous mixture with N 2 , a mixture of key interest in electrical applications. The effect of pore size, pressure, and mixture compositions on the selective adsorption of SF 6 was investigated by using Grand Canonical Monte Carlo simulations with simple fluid models and a simplified model of MCM-41. Simulations performed with multisite fluid models confirm that general trends are predicted using sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…At y SF6 : y N2  = 0.1:0.9, the selectivity was 44 in the internal nanopores at 1 atm, which was equivalent to the greatest selectivity value determined in previous studies, as shown in Table 1111213. Thus, the results of this study indicated that the wide nanopores with large pore volumes provided the greatest selectivity—yielding values similar to the greatest values achieved previously in extremely narrow nanopores, under ambient conditions—although grand canonical Monte Carlo simulations suggested that wide nanopores rarely show separation abilities at high pressures14.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…At y SF6 : y N2  = 0.1:0.9, the selectivity was 44 in the internal nanopores at 1 atm, which was equivalent to the greatest selectivity value determined in previous studies, as shown in Table 1111213. Thus, the results of this study indicated that the wide nanopores with large pore volumes provided the greatest selectivity—yielding values similar to the greatest values achieved previously in extremely narrow nanopores, under ambient conditions—although grand canonical Monte Carlo simulations suggested that wide nanopores rarely show separation abilities at high pressures14.…”
Section: Resultssupporting
confidence: 81%
“…SF 6 was preferentially adsorbed over N 2 in porous media, because of its strong adsorption potential; in contrast, SF 6 was rarely adsorbed in extremely narrow nanopores81112131415. SF 6 adsorption was rarely observed in zeolites with pores with a diameter of 0.5 nm, but N 2 was adsorbed easily in such narrow nanopores8; in contrast, zeolites with pores with a diameter of 1.0 nm selectively adsorbed SF 6 molecules over N 2 molecules11.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, efficient methods for the recovery or the decomposition of this gas should be developed because of its long-term effect on the environment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%